2020
DOI: 10.3390/microorganisms8060958
|View full text |Cite
|
Sign up to set email alerts
|

Variable Expression of Notch1 and Pax5 in Classical Hodgkin Lymphoma and Infection with Epstein–Barr in Pediatric Patients

Abstract: NOTCH1 and PAX5 participate in the proliferation and differentiation of B and T lymphocytes. Their expression can be modified by activation of NOTCH1, induced by the Epstein–Barr (EBV) viral proteins identified as LMP1 and LMP2. To identify whether PAX5, NOTCH1, and EBV latency genes participate in the oncogenic process of pediatric patients with classical Hodgkin lymphoma (cHL), the present study aimed to identify the variable expression of NOTCH1 among disease subtypes and to assess its effect on PAX5 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Some studies that have been carried out so far have shown that the percentage of viruses in Reed-Sternberg cells that are pathognomonic for Hodgkin's lymphoma, and that possessed a given virus, ranges up to over 70%. More precisely, over 70% of Reed-Sternberg cells and Stennerberg's cells had Epstein-Barr virus in them (19).…”
Section: Infectionmentioning
confidence: 99%
“…Some studies that have been carried out so far have shown that the percentage of viruses in Reed-Sternberg cells that are pathognomonic for Hodgkin's lymphoma, and that possessed a given virus, ranges up to over 70%. More precisely, over 70% of Reed-Sternberg cells and Stennerberg's cells had Epstein-Barr virus in them (19).…”
Section: Infectionmentioning
confidence: 99%
“…This Special Issue assembles eleven papers, comprising seven research articles, two reviews, and two brief reports, which collectively provide novel information on the mechanisms of oncogenesis [ 2 , 3 , 4 , 5 , 6 ] and viral replication [ 7 , 8 , 9 , 10 ], as well as applications for diagnosis [ 11 , 12 ].…”
mentioning
confidence: 99%
“…Using a variety of methods and approaches, several studies have provided a novel notion in understanding how EBV contributes to the development of various tumors, including GC [ 2 , 3 ], HL [ 4 ], NPC [ 5 ], and oral squamous cell carcinoma [ 6 ], on a molecular basis. A distinct feature of EBV-associated GC is the significant infiltration of immune cells in the epithelium, which appears to establish a unique tumor microenvironment.…”
mentioning
confidence: 99%
See 1 more Smart Citation